2008
DOI: 10.1186/1447-056x-7-6
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer in Iran: need for greater women awareness of warning signs and effective screening methods

Abstract: BackgroundBreast cancer remains an important public health problem. This study aimed to investigate about female knowledge of breast cancer and self-reported practice of breast self-examination in Iran.MethodsThis was a population-based survey carried out in Tehran, Iran. Data were collected via a structured questionnaire containing 15 questions on demographic status, history of personal and family breast problems, subjective knowledge about breast cancer covering its symptoms, the screening methods and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
233
12
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(290 citation statements)
references
References 44 publications
37
233
12
5
Order By: Relevance
“…Another two studies reported targeting socio-demographic variables were not effective for BSE practice (Parsa et al, 2008;Akhtari-Zavre et al, 2013). In contrast, other studies (Montazeri et al, 2008;Harirchi et al, 2012) reported that literacy was significantly correlated with a greater degree of knowledge about breast cancer, and literate women were significantly more likely to perform breast self examination.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Another two studies reported targeting socio-demographic variables were not effective for BSE practice (Parsa et al, 2008;Akhtari-Zavre et al, 2013). In contrast, other studies (Montazeri et al, 2008;Harirchi et al, 2012) reported that literacy was significantly correlated with a greater degree of knowledge about breast cancer, and literate women were significantly more likely to perform breast self examination.…”
Section: Discussionmentioning
confidence: 63%
“…However, several studies conducted in Iran demonstrated that usually women do not perform BSE (Ahmadian et al, 2012;Parsa et al, 2008). In a study by Noroozi et al (2011) 41.9% had performed BSE in the past and 7.6% of them performed it regularly and Montazeri et al (2008) study found that 63.0% of the women never performed a BSE in their lifetime. In the present study, majority of participants (97%) reported that they had hear about breast cancer but only 26% of them performed BSE.…”
Section: Discussionmentioning
confidence: 99%
“…Study done in educational institute of Lahore, Pakistan also reported television (14%) and hearsay (17%) as most common sources of information (Khokher, 2011). Similar evidence exists about electronic media and television being the most important sources of information on BC (Montazeri et al, 2010;Ravichandran et al, 2010;Yoo et al, 2012) followed by relatives and friends for less educated women (Hatefnia et al, 2010).…”
Section: Discussionmentioning
confidence: 63%
“…So, specific screening measures should be implemented for Iranian women and special programs should be considered for younger women (Mousavi et al, 2006;Harirchi et al, 2011). On the other hand Iranian studies indicated that the women's awareness of BC warning signs and effective screening were very inadequate (Yavari and Pourhoseingholi., 2007;Montazeri et al, 2008). Thus, health education program to rectify the lack of women awareness is urgently needed.…”
Section: Discussionmentioning
confidence: 99%